Treatment of Nasopharyngeal Carcinoma - Recent Advances - Khan, Arif Raza; Khan, Mohib Ullah; Khan, Saeed Ullah; Ullah, Hidayat (Journal of Postgraduate Medical Institute, 2011)
Many types of tumours, including rare; primitive ones have been described in the nasopharynx. Preliminary biopsy from the nasopharynx either from a mass or from the fossa of rossenmuller (Proof biopsies) is often required fro histodiagnosis of some tumours can be difficult of all the tumours carcinoma is the most common. It is unique in its epidemiology and racial predisposition with distinctive immunognetics influecing its prognosis and surviival. It is important to keep in mind that in all painless head and neck lumps malignancy must be suspected and a primary tumour in the nasopharynx can only the excludingly exhaustitive and expansive investigations includings CT Scan, MRI and biopsy. Nasopharyngeal carcinoma (NPC) and its metastasis often display fairly characteristics cytological and histological features in lymnph nodes, (cervical) which enable a presumptive diagnosis of their origin to be made. This would then alert the surgeon to search for the primary tumors and excising a lymp node, without prior examination by otolartgologist. Radiotherapy is the definitive treatment for nasopharyngeal carcinoma and its regional node metastasis.14